2010
DOI: 10.1073/pnas.1008937107
|View full text |Cite
|
Sign up to set email alerts
|

Binding of different histone marks differentially regulates the activity and specificity of polycomb repressive complex 2 (PRC2)

Abstract: The polycomb repressive complex 2 (PRC2) is the major methyltransferase for H3K27 methylation, a modification critical for maintaining repressed gene expression programs throughout development. It has been previously shown that PRC2 maintains histone methylation patterns during DNA replication in part through its ability to bind to H3K27me3. However, the mechanism by which PRC2 recognizes H3K27me3 is unclear. Here we show that the WD40 domain of EED, a PRC2 component, is a methyllysine histone-binding domain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
212
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(223 citation statements)
references
References 52 publications
(71 reference statements)
11
212
0
Order By: Relevance
“…Recently, two studies reported that EED, a component of PRC2, specifically binds to H3K27me3 via its C-terminal WD40 repeats and is responsible for the propagation of H3K27me3 to neighboring nucleosomes (44,45). We found that CDYL exhibits much stronger binding affinity for H3K27me3 than EED.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Recently, two studies reported that EED, a component of PRC2, specifically binds to H3K27me3 via its C-terminal WD40 repeats and is responsible for the propagation of H3K27me3 to neighboring nucleosomes (44,45). We found that CDYL exhibits much stronger binding affinity for H3K27me3 than EED.…”
Section: Discussionmentioning
confidence: 60%
“…EED is therefore thought to be responsible for the propagation of H3K27me3 marks to neighboring nucleosomes or the sister chromatid (44,45). Researchers have noted, however, that the affinity of EED for H3K27me3 is significantly weaker than that of HP1 and Pc chromodomains for the H3K9me3 or H3K27me3 peptides, suggesting additional readers may contribute to the recruitment of PRC2 to pre-existing H3K27me3 (45). We compared the binding affinity of CDYL and EED for H3K27me3 through semi-quantitative histone peptide binding assays.…”
Section: Cdyl Recognizes Histone Lysine 27mentioning
confidence: 99%
“…S3E). This mode of recognition differs from other WD40 domain peptide interactions involving basic motifs, such as recognition of modified arginine and lysine residues in histone tails, where aromatic cages stabilize the positive charges (30,31) (Fig. S4B).…”
Section: Mecp2mentioning
confidence: 97%
“…Most of the loop residues are invisible and the length of the loop varies among Nup43 orthologs. In contrast, another loop between b1A and b1B (resi [19][20][21][22][23][24][25][26][27][28][29][30], exhibits an ordered conformation in the crystal structure. It is solvent accessible and protrudes at the bottom surface which might allow it to contact the helix region of hNup85, as implied by the cryo-EM structure of Nup107 complex (Fig.…”
Section: Resultsmentioning
confidence: 98%